MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPS-1 PADA MATERI DAMPAK PENANGGULANGAN PENYAKIT MENULAR SEKSUAL MELALUI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) DI SMA NEGERI 1 SIGLI - Husaini Husaini (Jurnal Sains Riset, 2022)
This study aims to improve the learning achievement of students in class XI IPS-1 SMA Negeri 1 Sigli for the academic year 2020/2021 through learning the Problem Based Learning model. This research is a classroom action research (CAR) which is carried out in two cycles. Data analysis in this study is guided by the analysis of descriptive statistics with percentages. The data collection technique was done by written test, observation. Student activity is seen by using observation and test results. The results of this study indicate an increase in student learning outcomes from cycle I and cycle II. While the increase in learning outcomes is indicated by the increase in students whose scores reach the minimum completeness criteria as a whole. In the first cycle of 69.69% or as many as 23 students reached the minimum completeness criteria. In the second cycle there was an increase in students who achieved a minimum completeness score of 90.90% or as many as 30 students. So it can be concluded that the Application of the Problem Based Learning Model to Improve Student Learning in Class XI IPS-1 SMA Negeri 1 Sigli for the Academic Year 2020/2021.Keywords: Problem Based Learning, Learning Motivation, Learning Achievement.